2007
DOI: 10.1093/intimm/dxm136
|View full text |Cite
|
Sign up to set email alerts
|

LPS differentially regulates adhesion and transendothelial migration of human monocytes under static and flow conditions

Abstract: One of the key components of the innate immune response is the recognition of microbial products such as LPS by Toll-like receptors on monocytes and neutrophils. We show here that short-term stimulation of primary human monocytes with LPS led to an increase in adhesion of monocytes to endothelial cells and a dramatic decrease in transendothelial migration under static conditions. In contrast, under normal physiological flow, monocyte adhesion and migration across a human umbilical vein endothelial cell monolay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 58 publications
3
26
0
1
Order By: Relevance
“…A key aspect of this recruitment is the upregulation of adhesion molecules on endothelial cells by proinflammatory cytokines. Consistent with previous findings, we observed a vast increase in monocyte adhesion on TNF and flow-stimulated endothelium (Bradfield et al 2008). Using functional grade antibodies, we showed that in vitro adhesion mainly relies on CD11b/CD18-ICAM-1 interaction, also in agreement with previous findings (Ikuta et al 1991).…”
Section: Discussionsupporting
confidence: 93%
“…A key aspect of this recruitment is the upregulation of adhesion molecules on endothelial cells by proinflammatory cytokines. Consistent with previous findings, we observed a vast increase in monocyte adhesion on TNF and flow-stimulated endothelium (Bradfield et al 2008). Using functional grade antibodies, we showed that in vitro adhesion mainly relies on CD11b/CD18-ICAM-1 interaction, also in agreement with previous findings (Ikuta et al 1991).…”
Section: Discussionsupporting
confidence: 93%
“…CDK6 has been shown to play a role in the cell cycle but also cellular adhesion (25)(26)(27). LPS is a weak inducer of cellular proliferation, but it promotes cell adhesion.…”
Section: Inhibition Of Tnf-␣ Secretion and Adhesion By Cellsmentioning
confidence: 99%
“…Previous work has shown that adhesion of monocytes to the endothelium, the initial step in the development of atherosclerotic plaque, is increased by LPS stimulation of either human monocytes or HECs. 19,20 In this study, we assessed the effect of Lipo/GOT on monocyte adhesion to HECs induced by LPS. To this end, HEC and THP1 monocytes were first activated separately for 24 hours with LPS before starting the adhesion assay.…”
mentioning
confidence: 99%